1978
DOI: 10.1002/anie.197801271
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure of a Benzocyclobutadiene

Abstract: solvent is then removed under vacuum and the residue taken up in benzene, filtered and crystallized from pentane/toluene. 0.68g ZnC12 affords 2.7g (69%) (3a) [m.p. 77"C], while 0.92g CdC12 affords 2.848 (65%) ( 3 b ) [m.p. 94"C], and 1.41 g (Me3P)2NiC12 affords 3.0g (78 %) ( 3 c ) [m.p. 90°C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…1. Positional parameters as well as bond lengths and angles are listed in Tables 1 and 2 The molecular geometry of this compound is consistent with those of other bicyclo [4.2.0] octa-1,3,5trienes (Mak & Trotter, 1964;MacDonald, Lawrence & Cava, 1965;Hardgrove, Templeton & Templeton, 1968;Lawrence & MacDonald, 1969;Allen & Trotter, 1970a,b;Crawford & Marsh, 1973;Thummel, Korp, Bernal, Harlow & Soulen, 1977;Webber, Petcher & Loosli, 1977;Winter & Straub, 1978;Hart, Jeffares, Teuerstein & Ward, 1978;Thummel & Nutakul, 1978;Straub, D6ring & Winter, 1979;Korp & Bernal 1979;Ward, 1980;Hart, Teuerstein, Jeffares, Kung & Ward, 1980). The average Si-C(methyl) bond lengths are in agreement with recently published values (Hursthouse & Malik, 1979).…”
supporting
confidence: 71%
“…1. Positional parameters as well as bond lengths and angles are listed in Tables 1 and 2 The molecular geometry of this compound is consistent with those of other bicyclo [4.2.0] octa-1,3,5trienes (Mak & Trotter, 1964;MacDonald, Lawrence & Cava, 1965;Hardgrove, Templeton & Templeton, 1968;Lawrence & MacDonald, 1969;Allen & Trotter, 1970a,b;Crawford & Marsh, 1973;Thummel, Korp, Bernal, Harlow & Soulen, 1977;Webber, Petcher & Loosli, 1977;Winter & Straub, 1978;Hart, Jeffares, Teuerstein & Ward, 1978;Thummel & Nutakul, 1978;Straub, D6ring & Winter, 1979;Korp & Bernal 1979;Ward, 1980;Hart, Teuerstein, Jeffares, Kung & Ward, 1980). The average Si-C(methyl) bond lengths are in agreement with recently published values (Hursthouse & Malik, 1979).…”
supporting
confidence: 71%
“…Aromaticity and antiaromaticity, two essential concepts deeply ingrained in chemical thinking, are usually associated with Hückel's familiar 4n + 2 and 4n rules. Having both aromatic and antiaromatic behavior within the same molecule is uncommon; examples are limited to fused rings with 4n + 2 and 4n π electrons such as benzocyclobutadiene [1][2][3][4][5] and biphenylene. 3,4,6,7 As a rule, fused 4n + 2 and 4n rings both distort, leading to significant decreases of aromatic and antiaromatic character.…”
mentioning
confidence: 99%
“…Aromaticity and antiaromaticity, two essential concepts deeply ingrained in chemical thinking, are usually associated with Hückel’s familiar 4 n + 2 and 4 n rules. Having both aromatic and antiaromatic behavior within the same molecule is uncommon; examples are limited to fused rings with 4 n + 2 and 4 n π electrons such as benzocyclobutadiene and biphenylene. ,,, As a rule, fused 4 n + 2 and 4 n rings both distort, leading to significant decreases of aromatic and antiaromatic character. The analysis of the isotropic magnetic shielding , enveloping Ni II norcorrole (NiNc) and norcorrole (H 2 Nc) shows that these molecules provide unusual examples of conjugated systems with high antagonistic levels of antiaromaticity and aromaticity.…”
mentioning
confidence: 99%
“…NMR shifts of δ 6.26 and 5.78 were attributed to the benzene ring and δ6.36 to the olefin moiety. [32] Combined with crystallographic data, [33] the researchers suggested that 22 is nonaromatic and is better represented by 22 a (Scheme 5c).…”
Section: Benzocylobutadiene Biphenylenes and [N]phenylenesmentioning
confidence: 99%